A NEW SPECIES OF JANUS STEPHENS (HYMENOPTERA: CEPHIDAE) FROM INDONESIAN - DAVID R. SMITH SMITH (Treubia, 1994)
anus ecarinatus, n.sp., is described from western Kalimantan, Indonesia,This is the first record of the family Cephidae for Indonesia, the most southern in Asia, and one of the few know from the Southern Hemisphere. The absence of a genal carina and the long cercus are two of the significant characters that separate it from other species of Janus.